2019
DOI: 10.1109/access.2019.2919760
|View full text |Cite
|
Sign up to set email alerts
|

Secure Firmware Updates for Constrained IoT Devices Using Open Standards: A Reality Check

Abstract: While the IoT deployments multiply in a wide variety of verticals, the most IoT devices lack a built-in secure firmware update mechanism. Without such a mechanism, however, critical security vulnerabilities cannot be fixed, and the IoT devices can become a permanent liability, as demonstrated by recent large-scale attacks. In this paper, we survey open standards and open source libraries that provide useful building blocks for secure firmware updates for the constrained IoT devices-by which we mean lowpower, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 30 publications
0
73
0
Order By: Relevance
“…Regarding attacks directed to edge devices, a fundamental principle of the model is that they operate intermittently. This option drastically reduces the time window for attacks; for instance, those that exploit Over The Air (OTA) capabilities [18].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding attacks directed to edge devices, a fundamental principle of the model is that they operate intermittently. This option drastically reduces the time window for attacks; for instance, those that exploit Over The Air (OTA) capabilities [18].…”
Section: Discussionmentioning
confidence: 99%
“…Costin et al [32] conducted large-scale dynamic analysis of firmware and found vulnerabilities related to a Web interface; however, the scheme could not identify vulnerabilities in other modules of the firmware. Zandberg et al [33] proposed the possibility of creating a secure, standards-compliant firmware update solution that uses security technology to secure IoT devices.…”
Section: A Iot Firmware Analysismentioning
confidence: 99%
“…Some of them propose MQTT-based solutions ( [11][12][13]) and others propose customized/proprietary solutions [14,15]. Further, we discuss work in progress at the IETF [16][17][18].…”
Section: Related Workmentioning
confidence: 99%
“…Instead, our proposed MYNO Update Protocol uses a Nonce to avoid replay attacks. Zandberg et al [18] implemented and evaluated a prototype to compare the surveyed firmware update methods, among them the SUIT-OTA update. They use CoAP blockwise transfer to pull the firmware image onto the device.…”
Section: Related Workmentioning
confidence: 99%